Theory of Fixed Point on Fuzzy Metric Spaces and Their Solutions: Applications and Extensions (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The examination in this paper bargains basically with fixed point theorems and their applications. Fixed point theory on fuzzy metric space is blend of fuzzy set theory and fixed point theory. Fuzzy set theory has wide range applications because of idea of fuzzy set and fuzzy logic. The present paper is gone for acquiring a fixed point theorem on fuzzy metric space which fulfills a contractive condition. We are utilizing the idea of finish metric spaces in this theorem. Our result expands and sums up some result in fuzzy metric spaces. We likewise outfit an example which fulfills our primary result in this paper.